Offering a tailored return to work program to cancer survivors with job loss: a process evaluation - M. P. van Egmond; S. F. A. Duijts; A. P. J. Scholten; A. J. van der Beek; J. R. Anema (BMC, 2016)
Abstract Background In Europe, 1.7 million persons of working age are diagnosed with cancer each year. During or after treatment, cancer survivors (CSs) are vulnerable for job loss, and many CSs struggle with return to work (RTW). When offering RTW interventions to CSs, it is important to conduct a process evaluation to assess such factors as the population reached and implementation problems. Recently, we developed an innovative RTW program, tailored specifically to the needs of CSs with job loss in the Netherlands. The aim of this study was to evaluate the likelihood of theory and implementation failure, as well as to evaluate procedures for recruitment, execution and implementation of the tailored RTW program for CSs with job loss. Methods Six components were evaluated in the RTW program: Recruitment, Reach, Dosage, Implementation, Satisfaction, and Experienced Barriers. Data were provided by logbooks and questionnaires from participating CSs, occupational health care (OHC) professionals, and re-integration coaches and job hunting officers who delivered the RTW program. SPSS and Excel were used to conduct the analyses. Results 85 CSs received the tailored RTW program. Their mean age was 47.9 years (SD 8.5). The majority were female (72 %), married (52 %), and of Dutch nationality (91 %). The program reached 88.2 % of the target population and 52 % of participants who started the program received the adequate dosage. The program implementation score was 45.9 %. Participants' mean overall program duration remained within the protocol boundaries. Re-integration coaches were more satisfied with the program than job hunting officers or OHC professionals. Likewise, participants were more satisfied with the program delivery by the re-integration coaches than with the delivery by the job hunting officers. Reported barriers within the RTW program were a lack of communication, high program intensity and short program duration, and, with regard to the job hunting officers, a lack of experience with cancer-related RTW problems. Conclusions Participants, OHC professionals, re-integration coaches and job hunting officers generally had positive experiences with the innovative tailored RTW program. Facilitating communication between the delivering parties, and engaging usual care during program delivery, could be key elements to improved program implementation. Trial registration Dutch Trial Register, registration number NTR3562 , registered 07-08-2012.